2015
DOI: 10.1007/s10943-015-0133-3
|View full text |Cite
|
Sign up to set email alerts
|

Spirituality Moderates Hopelessness, Depression, and Suicidal Behavior among Malaysian Adolescents

Abstract: Suicide is an important public health problem for adolescents, and it is essential to increase our knowledge concerning the etiology of suicide among adolescent students. Therefore, this study was designed to examine the associations between hopelessness, depression, spirituality, and suicidal behavior, and to examine spirituality as a moderator between hopelessness, depression, and suicidal behavior among 1376 Malaysian adolescent students. The participants completed measures of depression, hopelessness, dail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 46 publications
3
10
0
5
Order By: Relevance
“…This adds support to previous studies suggesting that intrinsic religious motivation sustains individuals in stressful situations (Talib & Abdollahi, 2017), provides strength for today, meaning in life, spiritual experiences, hope for a good life, and hope for a tomorrow (Aghababaei et al, 2016;Koenig, 2009;Vail et al, 2010). These characteristics help individuals to believe that outcomes are encouraging and positive and provide a source of comfort during stressful situations (Abolfathi Momtaz et al, 2014;Talib & Abdollahi, 2017). The findings of this study also supported the moderating role of extrinsic religious motivation.…”
Section: Discussionsupporting
confidence: 86%
“…This adds support to previous studies suggesting that intrinsic religious motivation sustains individuals in stressful situations (Talib & Abdollahi, 2017), provides strength for today, meaning in life, spiritual experiences, hope for a good life, and hope for a tomorrow (Aghababaei et al, 2016;Koenig, 2009;Vail et al, 2010). These characteristics help individuals to believe that outcomes are encouraging and positive and provide a source of comfort during stressful situations (Abolfathi Momtaz et al, 2014;Talib & Abdollahi, 2017). The findings of this study also supported the moderating role of extrinsic religious motivation.…”
Section: Discussionsupporting
confidence: 86%
“…Among the factors that affect spirituality negatively are hopelessness, inability to take decisions independent of their parents in religious practice, and the fears and anxieties of adolescents with chronic illnesses (Spurr et al, 2013;Talib & Abdollahi, 2017;Weaver & Wratchford, 2017). In our study, all adolescents reported that negative feelings such as selfishness, lack of love, feeling of helplessness, insecurity, loneliness, jealousy, not being honest, hopelessness, emotional fatigue, stress, and exam anxiety were among the factors decreasing spirituality.…”
Section: Discussionmentioning
confidence: 54%
“…Spirituality generally emphasizes some basic elements, including purpose of life, hope, compassion, relationship, connectedness, and belief in the higher being (Chaar et al, 2018;Shek & Zhu, 2018). This concept can provide hope in highly desperate situations, can increase sense of closeness in individuals, can be a source of comfort and relief from stress, and can help pinpoint effective solutions to problems (Cotton et al, 2009;Luquis et al, 2012;Talib & Abdollahi, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher rates of suicide are registered among girls when compared to boys 10,12,14 , among adolescents who are exposed to physical and sexual violence [17][18][19] , who come from dysfunctional families with histories of psychopathology, and alcohol and drugs abuse 7,9,16 , and who abuse of alcohol and other drugs 12,20,21 . On the other hand, many studies have suggested that attending to religious institutions, being more exposed to religious beliefs, and paying more importance to religion reduces the chances of suicidal ideation, suicide attempts, and suicide itself [22][23][24][25][26][27] .…”
Section: Introductionmentioning
confidence: 99%